DIGITAL PEDAGOGIES IN DANCE EDUCATION: A NARRATIVE REVIEW OF MULTIMEDIA EFFECTIVENESS, CREATIVE LEARNING, AND IMPLEMENTATION BARRIERS - Md Sakek, Nur Arziana (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
The rapid expansion of digital technologies has reshaped the landscape of dance education, yet the pedagogical implications of this transformation remain unevenly understood. This narrative literature review examines how digital pedagogies influence learning across three interconnected domains: multimedia effectiveness, creative development, and the barriers that shape implementation. Synthesising findings from 20 peer-reviewed studies published between 2010 and 2025, the review highlights how multimedia tools, such as video analysis, mobile applications, virtual platforms, and interactive feedback systems, enhance technical performance, reflective practice, and learner engagement when aligned with sound pedagogical design. At the same time, digital environments expand creative possibilities, enabling new modes of choreographic exploration, interdisciplinary learning, and collaborative creation. However, the review identifies notable contradictions, including inconsistent measures of learning effectiveness, varied interpretations of creativity, and limited longitudinal evidence on sustained impact. Implementation challenges persist due to teacher readiness, institutional capacity, digital inequality, and cultural attitudes toward technology, reflecting an ongoing gap between technological potential and pedagogical reality. Theoretically, the review positions digital dance education as a dynamic system shaped by pedagogical intent, technological affordances, and contextual moderators. Practically, it underscores the need for strategic curriculum design, targeted teacher development, and equitable digital access. Future research should prioritise longitudinal designs, cross-cultural comparisons, and policy-oriented investigations to support a more sustainable and inclusive digital transformation in dance education.